Simulation of Helium Behavior Near Subsurface Prismatic Dislocation Loops in Tungsten. (2nd January 2017) - Hammond, Karl D.; Ferroni, Francesco; Wirth, Brian D.
Abstract : We analyze the effect of subsurface prismatic dislocation loops on the surface morphology and helium clustering behavior of plasma-facing tungsten through the use of molecular dynamics simulations that are moderately large in scale, consisting of approximately 830 000 atoms, and extend to times on the order of 1 μs. This approach eliminates some finite-size effects common in smaller simulations and reduces the flux to ∼5.5 × 10 26 m −2 s −1, including ions that reflect back into the plasma—this flux is a factor of ∼15 lower than is typically used in smaller simulations. These results indicate that prismatic loops with radii of ∼3 nm that are centered 10 nm below the surface with Burgers vectors parallel to the surface cause helium atom clusters to accumulate at the edge of the dislocation core relatively quickly—within 100 to 150 ns of the onset of plasma exposure. Subsequent growth of these clusters, however, is relatively minimal even out to 1 μs or more. This is partially explained by the relatively high helium implantation flux, which causes bubbles to accumulate 0 to 7 nm below the surface and block the region of the metal containing the dislocation, but this is only part of the explanation. Another effect results from the strain field around the loop itself. The compressive regions along the direction of the Burgers vector repel helium, but the tensile region initially attracts helium and traps it. However, we believe that the attractive tensile stress region is effectively shielded by the formation of helium clusters on and above it, and these bubbles subsequently experience relatively slow growth.